Performance Evaluation of Some Commercial Broiler Finisher Rations Sold in Nigeria - Uchegbu, M.C.; Igbokwe, N.O.; Omede, A.A.; Ekwuagana, I.C.; Okoli, I.C.; Esonu, B.O. (International Journal of Poultry Science, 2009)
A study was carried out with one-hundred and twenty 4-week old Hubbard broilers to compare the quality of some commercial feeds by assessing the performance of finisher broilers fed these diets. The commercial feed brands were collected and branded ZF, VF and EF. A formulated Control Feed (CF), T1 and three other commercial feeds ZF (T2), VF (T3) and EF (T4) were fed to the finisher broilers for 28 days in a completely randomized design experiment. The results showed that CF, VF and EF performed better than ZF in daily weight gain. Among the commercial feeds, however, VF achieved the fastest daily weight gain and therefore promoted the fasted growth rate, hence indicating a better balance in nutrient composition and improved feed quality.